PELAKSANAAN PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH OLEH ANGGOTA TIM YUNIOR PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI SULAWESI UTARA - Budiman, Rizal Y.; Sondakh, Jullie J.; Pontoh, Winston (Universitas Sam Ratulangi, 2015)
This study used a qualitative ethnographic method aimed to analyze the condition of the local government's financial statements examination by the examiner to the role of the Youth TeamÂ Member Audit Board and the things behind the condition. Data collected by means of interviews and observations at the time of examination of LKPD Talaud Islands and South Minahasa District for Fiscal Year 2013. The results showed that in the field of education and training of qualified inspectors have determined. In the examination of the planning process is not all examiners were involved in the preparation of the examination program while in the process of implementation of the inspection there are weaknesses such as inspection measures that can not be solved completely, different abilities to each examiner, and the preparation of paper checks that have not been fully resolved in the field . Furthermore, in the reporting process examiner had stints exceeding portion Youth Team Member.